Analysis of Public Service Quality at the Department of Industry and Trade of Biak Numfor Regency - Hamungkasi, Istiaji Gatut; Amiruddin, Amiruddin; Utami, Ayu Kurnia; Djunaedi, Djunaedi (Yayasan Gema Bina Nusantara, 2025)
This study aims to determine the Quality of Public Services at the Industry and Trade Office of Biak Numfor Regency. To determine the factors that are obstacles to the Quality of Public Services at the Industry and Trade Office of Biak Numfor Regency. The type of research used is a qualitative descriptive research type in this approach. Qualitative descriptive is a type of research that aims to describe all types of existing conditions, be it natural phenomena or man-made events, the conditions in question can be like forms, activities, characteristics, relationships, changes, differences, and similarities. The results of the study indicate that the quality of service at the Industry and Trade Office of Biak Numfor Regency is seen from its measurement using 5 indicators of service quality as follows: Tangible indicator, Reliability indicator, Responsibility indicator, Assurance indicator, Empathy indicator, from the five indicators show positive results (good). However, in the Tangible indicator in the sub-indicator of employee punctuality in entering the office is still lacking in providing services, the Industry and Trade Office of Biak Numfor Regency opens at exactly 08.00. Wit but there are still employees who are late not in accordance with the service hours posted on the notice board and also the Responsibility indicator, there is a response to complaints from users of this service that is less than optimal. This can be seen from the minimal participation of service users in providing suggestions and criticisms of the services available at the Industry and Trade Office of Biak Numfor Regency. Factors that hinder the quality of service at the Industry and Trade Office of Biak Numfor Regency are lack of Competence of Human Resources of the Apparatus in carrying out service tasks in the field and lack of facilities and infrastructure. So, this is a factor that is an obstacle in the field in providing services at the Industry and Trade Service of Biak Numfor Regency.